2023
DOI: 10.3390/jcm12165205
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Depressive Symptoms with Subjective Cognitive Decline in Elderly People—A Cross-Sectional Analysis from the AgeWell.de-Study

Abstract: To develop effective dementia prevention strategies, it is necessary to understand risk factors, associated factors and early signs of dementia. Subjective cognitive decline (SCD) is the earliest form of dementia. The aim of this study is to assess depression as a factor that is significantly associated with SCD. The data of 1030 general practitioner patients from the AgeWell.de-study (60–77 years; CAIDE dementia risk score ≥ 9) were analysed. A descriptive analysis was conducted using validated instruments li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…( 27 ) More recently, Zollinger et al suggested that depressive symptoms were associated with a higher prevalence of cognitive decline, in a German population. ( 26 ) Finally, in a study involving Brazilian subjects, cognitive and functional impairment were associated with higher levels of depressive symptoms. ( 28 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 27 ) More recently, Zollinger et al suggested that depressive symptoms were associated with a higher prevalence of cognitive decline, in a German population. ( 26 ) Finally, in a study involving Brazilian subjects, cognitive and functional impairment were associated with higher levels of depressive symptoms. ( 28 )…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are aligned with previous studies investigating the association between depressive symptoms and memory loss. ( [26] , [27] , [28] ) For example, in an ongoing longitudinal study, Wilson et.al suggested that the risk of Alzheimer's disease was increased in patients with depressive symptoms, measured with CES D-8 score. ( 27 ) More recently, Zollinger et al suggested that depressive symptoms were associated with a higher prevalence of cognitive decline, in a German population.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt the prevalence of depression among elderly above 60 years old the prevalence ranged from 23.7% to 74.5% for elderly in residential and household communities [13], 37.5% for older adults in geriatric homes, and 72% for inpatient [14]. Both SCD and depression were found to be risk factors to each other, as older population with SCD are more prone to develop depression than the those without SCD [15]. On the other hand, depressed individuals have higher risk to progress to SCD compared to the non-depressed.…”
Section: Introductionmentioning
confidence: 99%